Impact of TIC on the Internet massification after the implementation of Government Plan "Vive Digital" 2010 - 2014 in Colombia (2016)
This article shows the progress and actions taken government policy following the implementation of the plan "digital lives" in period 2010-2014 in the government of Juan Manuel Santos current President, seeking thereby to a great technological leap by the massification of internet the development of national digital ecosystem responding to the challenge of achieving democratic prosperity with the ownership and use of technology , thus generating , increased employment and poverty reduction that may lead to great social and economic benefits to Colombia.